Sintering, microstructure and properties of WC-AISI304 powder composites - Marques, B. J.
Tungsten carbide-stainless steel (AISI 304) based composites were successfully prepared by powder metallurgy routes using vacuum sintering at a maximum temperature of 1500 degrees C. The effects of the binder amount (between 6 and 15 wt.%) on the phase composition, microstructure and mechanical properties, namely hardness and fracture toughness, were investigated. Appreciable amount of (M,W)(6)C up to 12 wt.% was detected, especially for the higher SS contents. However, a good compromise between toughness and hardness was observed. Besides that, improved oxidation resistance was noticed in WC-SS based composites compared with WC-Co composites. The results are discussed having in mind the correlation between chemical composition, phase composition, microstructure and mechanical behavior. (C) 2013 Elsevier B. V. All rights reserved.